Strategi Penyediaan Access Reform pada Program Reforma Agraria di Kecamatan Jasinga, Kabupaten Bogor - Ana Anida; Arief Daryanto; Dudi S. Hendrawan (School of Business, Bogor Agricultural University (SB-IPB), 2018)
Agrarian reform, a resultant of land and access reforms, is targeted to reduce poverty and increase people’s welfare. The research aimed to analyze the main priority of the strategy, examine the implementation of the main strategies, and formulate the managerial implications. The data were analyzed using SWOT and QSPM. The results of SWOT analysis showed that strategic factors affect the implementation of access reform provision of agrarian reform. There are four strategic factors on strengths, six factors on weaknesses, three factors on opportunities, and four factors on threats. The main strategy in implementing access reform is W-O strategy i.e. the encouragement of community empowerment by providing several facilitations. The implementation of the main strategy in providing access reform in agrarian reform program has not been executed optimally. Therefore, strong commitment is needed, especially by the Land Registry Office of Bogor Regency. Based on the results, the researchers suggest the improvement of managerial implications such as the realization of integrated strategy for the access reform; specifically, to map the social economic potency, formulate the action planning, and maintain the continuity of the implementation of activities related to agrarian reform.Keywords: land reform, agrarian reform, access reform, SWOT, QSPMAbstrak: Reforma agraria yang merupakan resultant dari land reform dan acces reform, ditujukan untuk mengentaskan kemiskinan dan meningkatkan kesejahteraan rakyat. Penelitian bertujuan menganalisis strategi prioritas utama, menganalisis implementasi strategi prioritas serta serta merumuskan implikasi manajerialnya. Analisis yang digunakan adalah SWOT dan QSPM. Hasil analisis SWOT, terdapat faktor strategis yang memengaruhi pelaksanaan kegiatan penyediaan access reform reforma agraria, yaitu empat faktor strategis pada varibel kekuatan (strength), enam faktor pada varibel kelemahan (weakness), tiga faktor pada varibel peluang (opportunity), dan empat faktor pada varibel ancaman (threats). Strategi yang menjadi prioritas utama dalam pelaksanaan kegiatan penyediaan access reform adalah strategi W-O, yakni mendorong kegiatan pemberdayaan masyarakat/access reform melalui pemberian aneka jenis fasilitasi. Implementasi strategi prioritas pelaksanaan kegiatan penyediaan access reform dalam program reforma agraria di Kecamatan Jasinga belum dapat dijalankan secara optimal sehingga diperlukan komitmen yang lebih keras lagi, khususnya bagi jajaran Kantor Pertanahan Kabupaten Bogor untuk mentuntaskan program reforma agraria. Implikasi manajerial yang dapat direkomendasikan dalam kelanjutan pelaksanaan kegiatan penyediaan access reform dalam program reforma agraria di Kecamatan Jasinga adalah kegiatan pemberian access reform mengharuskan penerapan strategis secara terpadu yang dimulai dari tahapan pemetaan potensi sosial ekonomi, perumusan rencana aksi dan menjaga kesinambungan pelaksanaan kegiatan yang terkait reforma agraria. Kata kunci: land reform, reforma agraria, access reform, SWOT, QSPM